DEVELOPING MATHEMATICS STUDENT WORKSHEET BASED ON CONTEXTUAL IN MATERIAL TRIGONOMETRY ON THE X GRADE SENIOR HIGH SCHOOL - Aulia Hakim Yuslima; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The background study of this research is the school still at least worksheets based on contextual in the mathematics subject in the x grade of senior high school. This research uses design research to design a worksheet. The aims of this research are to develop a worksheet based on contextual and to know the validity criteria in material aspect, media aspect, and student's response. This research uses R & D research. The development of the worksheet includes: (a) gathering information, (b) design for worksheet, (c) doing validity in the expert, and (d) doing revision. For the proper of the worksheet includes: (a) tested, (b) analyze data, and (c) the proper of worksheet criteria. The subject of this research are the matter expert, media expert, mathematics teacher, and the students. This research using descriptive-quantitative data to describe the suggests from the matter expert, media expert, mathematics teacher, and the students through worksheets based on contextual which is developed. Â The result of this research can develop a worksheet based on contextual in trigonometry of x grade students. The mean of this result is 114,333 and the highest score is 130 in very good criteria for material aspect. In the media aspect, the mean is 101 and the highest score is 110 in very good criteria. In the student's response, the mean of the cluster score is 110,03 and the highest score is 130 in very good criteria. This result shows that the worksheet can be used for teaching and learning.